2019
DOI: 10.1088/1361-6560/aaf4de
|View full text |Cite
|
Sign up to set email alerts
|

Radioluminescence in biomedicine: physics, applications, and models

Abstract: The electromagnetic spectrum contains different frequency bands useful for medical imaging and therapy. Short wavelengths (ionizing radiation) are commonly used for radiological and radionuclide imaging and for cancer radiation therapy. Intermediate wavelengths (optical radiation) are useful for more localized imaging and for photodynamic therapy. Finally, longer wavelengths are the basis for magnetic resonance imaging and for hyperthermia treatments. Recently, there has been a surge of interest for new biomed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 127 publications
2
50
0
Order By: Relevance
“…[63][64][65] In vacuum CL has a broad spectrum that varies as a function of wavelength, , as −2 . [66] Due to light absorption and scattering in tissue and its components (water, hemoglobin, lipids), the effective CL spectrum in tissue has a complex shape, with a maximum around 650 nm. [67][68][69][70] The estimated photon yield of the Cherenkov process from clinical radionuclides is rather low, ≈1-50 photons per decay, corresponding to ≈12 000 photons per Bq for 18 F and ≈199 000 for 68 Ga. [66] The Cherenkov photon yield from 5 to 20 MeV X-ray photon beams is 60-100 photons per deposited MeV of energy.…”
Section: Light Generation By Radiation: Cherenkov Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…[63][64][65] In vacuum CL has a broad spectrum that varies as a function of wavelength, , as −2 . [66] Due to light absorption and scattering in tissue and its components (water, hemoglobin, lipids), the effective CL spectrum in tissue has a complex shape, with a maximum around 650 nm. [67][68][69][70] The estimated photon yield of the Cherenkov process from clinical radionuclides is rather low, ≈1-50 photons per decay, corresponding to ≈12 000 photons per Bq for 18 F and ≈199 000 for 68 Ga. [66] The Cherenkov photon yield from 5 to 20 MeV X-ray photon beams is 60-100 photons per deposited MeV of energy.…”
Section: Light Generation By Radiation: Cherenkov Effectmentioning
confidence: 99%
“…[66] Due to light absorption and scattering in tissue and its components (water, hemoglobin, lipids), the effective CL spectrum in tissue has a complex shape, with a maximum around 650 nm. [67][68][69][70] The estimated photon yield of the Cherenkov process from clinical radionuclides is rather low, ≈1-50 photons per decay, corresponding to ≈12 000 photons per Bq for 18 F and ≈199 000 for 68 Ga. [66] The Cherenkov photon yield from 5 to 20 MeV X-ray photon beams is 60-100 photons per deposited MeV of energy. [66] The latter value can be related to the radiation dose where for 1 Gy radiation dose, ≈5 × 10 11 Cherenkov photons are generated per cm 3 of tissue.…”
Section: Light Generation By Radiation: Cherenkov Effectmentioning
confidence: 99%
“…It has been demonstrated that the radioluminescence-yield of nanoscintillators can only enable low-dose PDT, [29][30][31][32] which hints toward the existence of other non-negligible therapeutic contributions of the nanoscintillators to explain the promising reported efficacies. First and foremost, as nanoscintillators are often composed of high-Z elements, we hypothesize that a radiation dose-enhancement effect exists when these materials are used for radiotherapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Once this process is repeated for the entire set of 10,000 images, the positions of all detected events are aggregated into a single image, where each pixel represents the number of radioactive decay events detected at that location. Detailed reconstruction procedures and radioluminescence imaging can also be found from our previous papers [ 14 , 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%